Effect of Processing on the Nutritional Quality of Ilex paraguariensis - Maria Rosana Ramirez; Leandro Mohamad; Lilian Celeste Alarcon-Segovia; Ignacio Rintoul (Applied Sciences, 2022)
Ilex paraguariensisA.St.-Hil. (IP) is a South American plant. IP-dried leaves have been consumed in the form of infusion by indigenous peoples since pre-Hispanic times. In recent years, IP has gained many beverage markets and new ways of consumption, reaching the category of a global consumer product. A side consequence is the increase in IP crops for the specification of human consumption. This situation is the driving force for the investigation of new uses of IP, including feed supplements for livestock and functional food for human consumption. A deep understanding of the influence of processing on the nutritional value of IP is crucial for the development of these alternative products. It is known that the quality and quantity of nutritional compounds occurring in IP depend on the origin, plant condition, and harvest time. However, the effects of the drying method of the leaves and the ageing time of dried leaves on the final IP products deserve further investigation. The present work presents the variation of the nutritional, digestibility, energy, and mineral assets of IP submitted to three different processes: open-air dried and crushed; dried under direct fire and grounded; and dried under direct fire, grounded, and aged for 6 months under controlled conditions. The presence of agrochemical residues and antinutritional factors were also studied. Processing widely influenced the nutritional and digestibility assets of IP leaves. The inorganic content (K, Mg, Ca, P, Zn, B and Fe) significantly varied among leaves treated using different processes. IP samples dried in open air resulted in the highest % of crude protein, Mg, K, S, and Mn. IP samples dried under direct fire resulted in the highest % of carbohydrates and Fe. IP samples dried under direct fire and aged for 6 months resulted in the highest % of digestible matter, Ca, P, Zn, and B. The results also showed quality protein levels between 10.03 and 19.06% of dry matter. The digestibility values showed that IP leaves are suitable for human functional foods and for enriched supplements for livestock feeds. No traces of agrochemicals or antinutritional factors were found.